ÙØ¹Ø§Ù„ÙŠØ© Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙƒØªØ§Ø¨ Ø§Ù„ØµØ±Ù Ù„Ù„Ù…Ø³ØªÙˆÙ‰ Ø§Ù„Ø«Ø§Ù†ÙŠ Ù…Ù† Ø³Ù„Ø³Ù„Ø© ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„ØªÙ†Ù…ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© Ù„Ø¯Ù‰ Ø·Ø§Ù„Ø¨ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø«Ø§Ù†ÙŠ Ø§Ù„Ø¹Ø§Ù„ÙŠØ© Ø¨Ù…Ø¹Ù‡Ø¯ Ù†ÙˆØ± Ø§Ù„Ø¥Ø³Ù„Ø§Ù… ØºÙ†ØªÙŠ Ù„Ù…Ø¨ÙˆÙƒ Ø§Ù„ÙˆØ³Ø·Ù‰ - Josman, Yosal; Ardiani, Ika Tri (Program studi Pendidikan Bahasa Arab UNNES, 2021)
Ù„Ù‚Ø¯ Ù‚Ø§Ù… Ø§Ù„Ø¨Ø§ØØ« Ø¨Ù…Ø´Ø§Ù‡Ø¯Ø© ÙˆÙ…Ù„Ø§ØØ¸Ø© ØªØ·Ø¨ÙŠÙ‚ ÙˆØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ ÙØµÙ„ Ø§Ù„Ø«Ø§Ù†ÙŠ Ø§Ù„Ø¹Ø§Ù„ÙŠØ© Ø¨Ù…Ø¹Ù‡Ø¯ Ù†ÙˆØ± Ø§Ù„Ø§Ø³Ù„Ø§Ù… ØºÙ†ØªÙŠ ÙÙˆØ¬Ø¯ Ø§Ù„Ø¨Ø§ØØ« Ø¨Ø¹Ø¶ Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª Ø§Ù„Ù„ØºÙˆÙŠØ© Ø®ØµÙˆØµØ§ ÙÙŠ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø©ØŒ Ù…Ù†Ù‡Ø§ Ø¹Ø¯Ù… Ø§Ù„Ù…Ù…Ø§Ø±Ø³Ø© Ø¹Ù„Ù‰ Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ø¬Ù‡Ø±ÙŠØ©ØŒ Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù…ØªÙ‚Ø·Ø¹Ø©ØŒ Ø§Ù„Ù‚ÙØ² Ø¹Ù† Ø¨Ø¹Ø¶ Ø§Ù„ÙƒÙ„Ù…Ø§ØªØŒ Ø§Ù„ØªÙƒØ±Ø§Ø± ÙÙŠ Ø§Ù„Ù‚Ø±Ø§Ø¡Ø©ØŒ Ø¹Ø¯Ù… Ù…Ø¹Ø±ÙØ© Ù‚ÙˆØ§Ø¹Ø¯ Ø§Ù„ØµØ±ÙÙŠØ©. ÙˆÙˆØ¬Ø¯ Ø§Ù„Ø¨Ø§ØØ« Ø¨Ø¹Ø¶ Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª Ø§Ù„Ù†ÙØ³ÙŠØ© Ù…Ù†Ù‡Ø§ Ø¥Ù‡Ù…Ø§Ù„ Ø§Ù„Ù…Ø¹Ù„Ù…ØŒ Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© Ø¨Ù„Ø§ Ø±ØºØ¨Ø© ÙˆØ§Ù„Ø§Ù‡ØªÙ…Ø§Ù…. ÙˆØ§Ù„Ø£Ø³Ø³ Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª Ø§Ù„Ù…Ø°ÙƒÙˆØ±Ø© ÙÙŠ Ø§Ù„Ø³Ø§Ø¨Ù‚Ø© Ù‡Ùˆ Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© ÙŠØ¹Ù†ÙŠ Ø§Ù„ÙƒØªØ§Ø¨ Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù… ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ù„ÙŠØ³ Ø§Ù„ÙƒØªØ§Ø¨ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠ. Ø¨Ù†Ø§Ø¡Ø§ Ø¹Ù„Ù‰ Ù‡Ø°Ù‡ Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª Ù‚Ø§Ù… Ø§Ù„Ø¨Ø§ØØ« Ø¨Ø§Ù„Ø¨ØØ« Ø§Ù„Ø°ÙŠ ÙŠÙ‡Ø¯Ù Ø¥Ù„Ù‰ Ù…Ø¹Ø±ÙØ© Ù…Ø¯Ù‰ ÙØ¹Ø§Ù„ÙŠØ© Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙƒØªØ§Ø¨ Ø§Ù„ØµØ±Ù Ù„Ù„Ù…Ø³ØªÙˆÙ‰ Ø§Ù„Ø«Ø§Ù†ÙŠ Ù…Ù† Ø³Ù„Ø³Ù„Ø© ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„ØªÙ†Ù…ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© Ù„Ø¯Ù‰ Ø·Ù„Ø§Ø¨ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø«Ø§Ù†ÙŠ Ø§Ù„Ø¹Ø§Ù„ÙŠØ© Ø¨Ù…Ø¹Ù‡Ø¯ Ù†ÙˆØ±Ø§Ù„Ø§Ø³Ù„Ø§Ù… ØºÙ†ØªÙŠ ÙˆÙ„Ù…Ø¹Ø±ÙØ© Ø·Ø±ÙŠÙ‚Ø© ØªØ¹Ù„ÙŠÙ… Ø³Ù„Ø³Ù„Ø© ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø§Ø¨ÙŠØ© ÙˆÙØ¶Ù„ Ø§Ù„Ø¨Ø§ØØ« Ù…Ù†Ù‡Ø¬ÙŠØ© Ø§Ù„ÙƒÙ…ÙŠØŒ Ù„Ø£Ù† Ø§Ù„Ø¨Ø§ØØ« Ø§Ø³ØªØ®Ø¯Ù… Ù†ÙˆØ¹ Ø§Ù„Ø¨ØØ« Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠ. ÙˆØ¨Ø¹Ø¯ Ø§Ù„Ù‚ÙŠØ§Ù… Ø¨Ø§Ù„ØªØ¬Ø±Ø¨Ø© ÙˆØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ØØµÙ„ Ø§Ù„Ø¨Ø§ØØ« Ø¹Ù„Ù‰ Ø®Ù„Ø§ØµØ© ÙˆÙ‡ÙŠ Ø£Ù† Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙƒØªØ§Ø¨ Ø§Ù„ØµØ±Ù Ù„Ù„Ù…Ø³ØªÙˆÙ‰ Ø§Ù„Ø«Ø§Ù†ÙŠ Ù…Ù† Ø³Ù„Ø³Ù„Ø© ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„ØªÙ†Ù…ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© ÙØ¹Ø§Ù„. Ø§Ø¹ØªÙ…Ø§Ø¯Ø§ Ø¹Ù„Ù‰ Ø§Ù„Ù†ØªØ§Ø¦Ø¬ Ø§Ù„ØªÙŠ ØØµÙ„ Ø¹Ù„ÙŠÙ‡Ø§ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„Ù‚Ø¨Ù„ÙŠ ÙˆØ§Ù„Ø¨Ø¹Ø¯ÙŠ. Ù…Ø¹Ø¯Ù„ Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ Ø§Ù„Ø§Ø®Ø¨Ø§Ø± Ø§Ù„Ù‚Ø¨Ù„ÙŠ Ù‡ÙŠ 52,50 ÙˆØªÙƒÙˆÙ† Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„Ø¨Ø¹Ø¯ÙŠ Ù‡ÙŠ 90,00 ØªØ¯Ù„ Ø¹Ù„Ù‰ Ø£Ù† Ù†ØªØ§Ø¦Ø® Ø§Ù„Ø·Ù„Ø§Ø¨ ØªØ±ØªÙØ¹ Ø§Ø±ØªÙØ§Ø¹Ø§ Ø´Ø¯ÙŠØ¯Ø§ Ø¨Ø¹Ø¯ Ø§Ù„ØªØ¬Ø±Ø¨Ø© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙƒØªØ§Ø¨ Ø§Ù„ØµØ±Ù Ù„Ù„Ù…Ø³ØªÙˆÙ‰ Ø§Ù„Ø«Ø§Ù†ÙŠ Ù…Ù† Ø³Ù„Ø³Ù„Ø© ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©. ÙˆÙ‡Ø°Ø§ Ù…ÙˆØ«ÙˆÙ‚ Ø¨Ù†ØªÙŠØ¬Ø© Ø§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø©. The researcher saw and observed the application and teaching of the Arabic language in the second semester of the high school at the Nurul Islam Ganti Institute, and the researcher found some linguistic problems, especially in the skill of reading, including lack of practice in reading aloud, intermittent reading, skipping some words, repetition in reading, lack of knowledge of morphological rules. The researcher found some psychological problems, including neglect of the teacher, reading without desire and attention. The foundations of the problems mentioned in the previous one are educational problems, meaning the book used in this institute is not the educational book. Based on these problems, the researcher conducted research aimed at knowing the effectiveness of using the textbook for the second level of the Arabic language education series to develop the reading skill of the second semester high students of the Nurul Islam Ganti Institute and to know the method of teaching the Arabic language teaching series and the researcher preferred the quantitative method, because the researcher used the type empirical research. After doing the experiment and analyzing the data, the researcher got a conclusion, which is that using the exchange book for the second level of the Arabic language teaching series to develop reading skill is effective. Depending on the results obtained by students in the pretest and the post-test. The average results of the students in the tribal news is 52.50 and the post test is 90.00 indicating that the students â€™results rise dramatically after the experiment using the exchange book for the second level of the Arabic language teaching series. This is reliable with the outcome of the interview.